E-GOVERNMENT-BASED VILLAGE FUND MANAGEMENT TO ACHIEVE GOOD GOVERNANCE - Nurhaliza, Agid (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
In order to carry out good governance thru e-government for village fund management, an application called the Village Financial System (SISKEUDES) and Cash Management Systems (CMS) was launched. The maximum implementation of CMS & SISKEUDES can penetrate the process of village financial accountability. This research aims to examine how village funds are managed thru SISKEUDES & CMS to achieve good governance and what obstacles are faced in implementing e-government. This research uses a qualitative approach with field research conducted thru observation, interviews, and documentation. The data sources in this study include primary data sources. The data analysis technique and its process, which goes thru 4 stages (data import, data coding, visualization, and verification), use nvivo 14 pro software. The results of this study indicate that: The massive application of SISKEUDES and CMS in managing village funds significantly increases transparency, accountability, and community participation, and is in line with the principles of maqashid syariah, particularly hifz al-maal (protection of property). This study also found that the principles of good governance in Islam, which are present in the interpretation of Q.S Al-Hajj verse 41, such as shura, justice, accountability, trust, and a focus on the future, are also indirectly present in the use of e-government. The implementation of SISKEUDES and CMS in Lumpatan village still faces challenges, but these do not significantly impact the village's operational activities. The issues encountered are limited to poor signal strength and periodic system improvements.